The mirages of a rebelion : being Free French in Chad - (:unkn) unknown (My University, 2019)
My dissertation examines the impact of the collective disobedience on individual lives, colonial communities and the gaullist ideology in Chad during the Second World War. After a a dissent on the 26th August 1940, this seemingly remote and marginal African colony became a military and political laboratory in which General de Gaulle’s organization faced a great number of political, military and colonial challenges. This work tries to contribute to three ongoing scholarly debates : the choices that people make in wartime and their repercussions ; the profound and ambiguous effects by the Second World War on colonial empires and imperialism ; the dialectic between mobilization and demobilization in the personal writings and memories. Drawing on documents collected in French, British and American archives, I analyze the different ways in which Free French soldiers, colonial administrators and so-called “indigenous” people from Chad had a specific combat experience which reworked the links between the French motherland and its colonies. Moreover, these ambiguities had been strengthened by the desert war. The military operations in Southern Libya between 1941 and 1943 implied an unexpected war violence. The rebelion which founded the Free French Chad was considered as a problem even by the colonial officers and administrors who organized it during the summer 1940. They believed that it deeply undermined their legitimacy as rulers of the Empire. Warfare in Chad was therefore conceived as a way to produce a renewed elite for France after its liberation. Nonetheless, these great expectations were at variance with the poverty and the boredom which damaged the combat motivation of the Free French troops. Furthermore, the chiefs who appeared thanks to the colonial dissent and the desert war had great difficulties to realize how much the German Occupation had changed their homeland.
Keywords: African Research